Safety, tolerability, pharmacokinetics, and pharmacodynamics of novel glucokinase activator HMS5552: results from a first-in-human single ascending dose study - Xu HR; Sheng L; Chen WL; Yuan F; Yang MJ; Li H; Li XN; Choi J; Zhao GY; Hu TX; Li YG; Zhang Y; et al. (Dove Medical Press, 2016)
Hongrong Xu,1,* Lei Sheng,1,* Weili Chen,1 Fei Yuan,1 Mengjie Yang,1 Hui Li,1 Xuening Li,1 John Choi,2 Guiyu Zhao,2 Tianxin Hu,2 Yongguo Li,2 Yi Zhang,2 Li Chen2 1Department of Clinical Pharmacology, Zhongshan Hospital, Fudan University, Shanghai, 2Department of Clinical Research & Development, Hua Medicine, Shanghai, People’s Republic of China *These authors have contributed equally to this work Background: HMS5552, a novel fourth-generation glucokinase (GK) activator, has demonstrated promising effects on glycemic control in preclinical models of type 2 diabetes. This single ascending dose study was conducted to investigate the safety, tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) of HMS5552 during its first-in-human exposure.Methods: Sixty healthy subjects were enrolled. In each of six dose-cohorts (5, 10, 15, 25, 35, and 50 mg), ten subjects were randomized with eight subjects receiving the same cohort-dose of HMS5552 and two receiving placebo. Plasma HMS5552 exposure, glucose, and insulin were measured repeatedly during fasting and after a standardized meal. Assessment included safety, PK, and PD endpoints.Results: HMS5552 showed dose-proportional increases in area under the curve 0 to the last quantifiable concentration (AUC0–t) and maximum plasma concentration (Cmax). Slopes estimated by linear regression for AUC0–t and Cmax were ~1.0 (0.932 and 0.933, respectively). Geometric mean elimination half-life ranged from 4.48 to 7.51 hours and apparent clearance ranged from 11.5 to 13.1 L/h across all doses. No significant sex effect was observed in PK parameters. HMS5552 also demonstrated dose-related PD responses in terms of maximum glucose change from baseline (%) and mean glucose area under effect curve 0–4 hours change from baseline (%) (P<0.001). Fifteen adverse events were reported by nine subjects (ten with HMS5552 and five with the placebo). All adverse events were mild in intensity and resolved without any treatment.Conclusion: This first-in-human single ascending dose study provided predicted PK of HMS5552 with dose-proportional increases in AUC0–t and Cmax, as well as dose-related glucose-lowering effects over the range of 5–50 mg in healthy subjects. HMS5552 at doses up to 50 mg in healthy subjects was safe and well-tolerated. Keywords: HMS5552, glucokinase activator, type 2 diabetes, pharmacokinetics, pharmacodynamics